Pengaruh Kesenian Daerah Terhadap Sikap Moderasi Beragama dalam Mewujudkan Harmonisasi Sosial di Masyarakat Desa Cisantana Kabupaten Kuningan Jawa Barat - Rasidah, Hamidatur; Oktaviani, Fatimah; Choirunisa, Wanda; Thobibi, Mohammad Ghilman; Padantya Sakrura, Athaya Gusti Rakha; Uriawan, Wisnu (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
This study aims to analyze religious moderation attitudes through local arts in realizing social harmony in society. This research uses the Sisdamas KKN service method and a qualitative approach. Data is collected through literature studies sourced from scientific articles, books, and several other written works relevant to the research theme. The results of the study show that Cisantana village is so complex, seen in its community which has religious diversity and has many regional arts. Regional arts such as stage dance, lute and several other arts are one of the causes of the realization of harmonization in the CiSantana village community. Because of the diversity of religions in Cisantana village, it is also designated as a moderation village, and this can be seen in several artistic activities where people with a tolerant attitude move together regardless of the differences that exist.